The Analisis Kinerja Belanja Daerah dan Efektivitas Pajak Kabupaten Blitar Tahun 2019-2023 - Ardaningrum, Nandita; Fifi Aleyda Yahya; Marsella Dwi Jayanti; Yesi Ditaviani; Isyfa Qurrata Aini; Ulfatu Rohmah; Mega Tunjung Hapsari (CV. Kalimasada Group, 2024)
This research was conducted to assess the performance of regional spending and the effectiveness of taxes in Blitar Regency during 2019-2023. The raiso analysis used is the expenditure growth ratio, operating expenditure ratio, capital expenditure ratio and tax effectiveness ratio. The data collection method uses quantitative description. The research uses secondary data by looking for data from BPS sources and the Blitar Regency Ministry of Finance. The research discussion shows that the results of the Blitar Regency expenditure growth ratio analysis are not good, with the average expenditure growth being greater than income growth, namely 3.37% > 1.19%. Operating expenditure ratio with an average percentage of 56.42% with good performance criteria. The capital expenditure ratio obtained an average percentage of 16.08% with good expenditure performance criteria. Meanwhile, the tax effectiveness ratio obtained an average percentage of 118.62%, which means that tax performance is very effective.